Product Quality and Social Media Marketing on Brand Image and Purchase Decisions for Viva Cosmetics Products in Pekanbaru City Society - Amin, Amirudin M.; Khairani, Nadya Rahmi; Rusilawati, Ermina (First Ciera Publisher, 2024)
This study aimed to determine the effect of product quality and social media marketing on brand image and purchase decisions. This research was conducted in Pekanbaru, Riau. The population in this study was all the people of Pekanbaru, so using the Roscoe formula, the sample was set at 120 people using the accidental sampling method. Data analysis using multiple linear regression. Research results information that (1) product quality has a positive and significant influence on brand image. (2) social media marketing has a positive and significant influence on brand image. (3) product quality has a positive and significant influence on purchase decisions. (4) social media marketing has a positive and significant influence on purchase decisions. (5) brand image has a positive and significant influence on purchase decisions.